MITE PESTS OF HONEYBEE (APIS MELLIFERA L.) AND THEIR SEASONAL INCIDENCE IN JAMMU DIVISION OF JAMMU AND KASHMIR, INDIA - KOTWAL, SANDEEP; D. P. ABROL; A. SHAHNWAZ DAR; GANDOTRA, AMIT (The Bioscan, 2013)
Mites are serious enemies of honeybees. The studies on mites infesting honeybee Apis mellifera in Jammu region revealed the occurrence of Ectoparasitic mite Varroa destructor Anderson and Truemann, Tropilaelaps clareae Delfinado and Delfenado-Baker, Varroa jacobsoni Oudemans, Tropilaelaps koenigerum Delfinado and DelfenadoBaker., Phoretic mites Neocypholaelaps indica (Evans) and stored product mites Caloglyphus indica Tyrophagus longior (Gervais), Glyciphagus destructor and hypopus stages. However, endoparasitic Acarapis woodi (Rennie) was not detected in the present studies. Population dynamics of mites varied with different seasons of the year. The ectoparasitic mite Varroa destructor was found throughout the year with maximum abundance during March. However, stored product and the phoretic mites were observed during certain parts of the year.